Mutations in MBOAT7, Encoding Lysophosphatidylinositol Acyltransferase I, Lead to Intellectual Disability Accompanied by Epilepsy and Autistic Features - Johansen, Anide; Rosti, Rasim O; Musaev, Damir; Sticca, Evan; Harripaul, Ricardo; Zaki, Maha; Çağlayan, Ahmet Okay; Azam, Matloob; Sultan, Tipu; Froukh, Tawfiq; Reis, André; Popp, Bernt; et al. (American journal of human genetics, 2016)
The risk of epilepsy among individuals with intellectual disability (ID) is approximately ten times that of the general population. From a cohort of >5,000 families affected by neurodevelopmental disorders, we identified six consanguineous families harboring homozygous inactivating variants in MBOAT7, encoding lysophosphatidylinositol acyltransferase (LPIAT1). Subjects presented with ID frequently accompanied by epilepsy and autistic features. LPIAT1 is a membrane-bound phospholipid-remodeling enzyme that transfers arachidonic acid (AA) to lysophosphatidylinositol to produce AA-containing phosphatidylinositol. This study suggests a role for AA-containing phosphatidylinositols in the development of ID accompanied by epilepsy and autistic features.